2014
DOI: 10.1590/2317-1782/20142013071
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cleft type I in neonate: case report

Abstract: Laryngeal cleft (LC) is a congenital malformation that leads to the unusual communication between the esophagus and the laryngotracheal complex. It is a rare disease, mostly prevalent among male individuals. The goal of this study was to describe the evaluation and intervention by the speech language pathologist of a female newborn diagnosed with LC type I, admitted on the University Hospital of Universidade de São Paulo, in her second hospitalization due to small weight gain and pneumonia. She was submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…5 The condition is usually associated with gastroesophageal reflux disease and genetic syndromes such as Pallister-Hall syndrome, CHARGE syndrome, VACTERL association, Opitz G/BBB syndrome, and DiGeorge syndrome. 6 Presenting clinical symptoms include coughing, cyanosis, aspiration, and choking events, as were noted with our patient. Because neonates often show suck, swallow, and breathing incoordination, 7 the diagnosis of LC is often missed or delayed.…”
supporting
confidence: 66%
“…5 The condition is usually associated with gastroesophageal reflux disease and genetic syndromes such as Pallister-Hall syndrome, CHARGE syndrome, VACTERL association, Opitz G/BBB syndrome, and DiGeorge syndrome. 6 Presenting clinical symptoms include coughing, cyanosis, aspiration, and choking events, as were noted with our patient. Because neonates often show suck, swallow, and breathing incoordination, 7 the diagnosis of LC is often missed or delayed.…”
supporting
confidence: 66%
“…There is a vast bibliography on the benefits of flow control in the prevention of swallowing problems by reducing the flow, limiting the exit with slow flow holes, and/or thickening the liquid. 35 36 37 38 39 Given that, it can be concluded that in the translactation technique with urethral catheter number 6 or even 8, the flow is tightly controlled, even with the supposed increase in flow due to the ejection of mother's milk in a normal process of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genetic syndromes such as Opitz-Friaz syndrome, Pallister-Hall syndrome, DiGeorge syndrome, CHARGE syndrome, and VACTERL association are also known to be frequently associated with laryngeal clefts (33).…”
Section: Comorbidities and Associationsmentioning
confidence: 99%
“…Medical management of associated comorbidities aims to improve disorders that may contribute to the swallowing impairments. On the other hand, feeding therapy involves modification to feed thickness, feeding adjuncts, positional strategies and maneuvers to prevent aspiration (6,15,19,22,33). In a research survey by Yeung et al (1), the majority of clinicians recommended anti-reflux therapy only in the presence of laryngopharyngeal reflux symptoms.…”
Section: Conservative Managementmentioning
confidence: 99%
See 1 more Smart Citation